Analysis of the 2002 World Championships in Tehran, Moscow and Chalkida - Tünnemann, H. (2002)
FILA Coaches Clinic December 2002 in ROME 0 Comprehensive aspects 1. State of performance and development of freestyle wrestling 1.1 Country-specific aspects 1.2 Qualitative analysis of combat behaviour 2. State of performance and development of Greco-Roman wrestling 2.1 Country-specific aspects 2.2 Qualitative analysis of combat behaviour 3. State of performance and development of women's wrestling 3.1 Country-specific aspects 3.2 Qualitative analysis of combat behaviour 4. Special aspects of the clinch